The main drivers of a rise in the non-performing loans ratio: case study for Portugal banking sector - Santos, Maria Catarina Silva Maltez (2022)
Dissertation presented as the partial requirement for obtaining a Master's degree in Statistics and Information Management, specialization in Risk Analysis and Management